2021
DOI: 10.1155/2021/6649524
|View full text |Cite
|
Sign up to set email alerts
|

How Did the COVID-19 Pandemic Affect Higher Education Learning Experience? An Empirical Investigation of Learners’ Academic Performance at a University in a Developing Country

Abstract: COVID-19 has dramatically reshaped the way global education is delivered. Millions of learners were affected by educational institution closures due to the pandemic, which resulted in the largest online movement in the history of education. With this sudden shift away from classrooms in many parts of the globe, universities had to rapidly shift to virtual and digital strategies. Many believe that the adoption of online distance learning will persist after pandemic. A new hybrid model of education is expected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
170
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 12 publications
11
170
2
10
Order By: Relevance
“…The impact of DE on academic performance has been little explored, and the research has shown contradictory results. An Egyptian study did not find any statistically significant difference in students’ academic learning and performance in the shift from face-to-face to online DE due to the COVID-19 lockdown [ 60 ]. A significant positive effect of COVID-19 confinement on students’ performance was reported by Gonzalez et al [ 42 ], who showed that students’ learning strategies became more continuous habits, improving their efficiency and autonomous learning performance.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of DE on academic performance has been little explored, and the research has shown contradictory results. An Egyptian study did not find any statistically significant difference in students’ academic learning and performance in the shift from face-to-face to online DE due to the COVID-19 lockdown [ 60 ]. A significant positive effect of COVID-19 confinement on students’ performance was reported by Gonzalez et al [ 42 ], who showed that students’ learning strategies became more continuous habits, improving their efficiency and autonomous learning performance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies underscored the different actions of the Higher Educational Institutions (HEI's) all over the world in securing the health of the students as well as the academic personnel, and likewise in mitigating the spread of coronavirus or COVID-19. Most of HEI's closed the schools in March 2020 and shifted their paradigm from face-to-face to distance or remote learning (Almazova et al, 2020;Balakrishnan, 2020;Bozkurt et al, 2020;CHED, 2020;Ghazi-Saidi et al, 2020;Goncalves, 2020;Habaragoda, 2020;Karademir et al, 2020;Mukherjee & Hasan, 2020;& Refaat El Said, 2020).…”
Section: Implication Of the Action Researchmentioning
confidence: 99%
“…The COVID-19 pandemic was announced by World Health Organization (WHO) in March 2020 (WHO, 2020). As response to mitigate the spread of the coronavirus, most Asian countries declared lockdown on March 16, 2020 (Balakrishnan, 2020;Bozkurt et al, 2020), and shifted their paradigm from face-to-face to distance learning or remote learning to secure the health of the students as well as the teachers (Almazova et al, 2020;Balakrishnan, 2020;Bozkurt et al, 2020;Ghazi-Saidi et al, 2020;Goncalves, 2020;Habaragoda, 2020;Karademir et al, 2020;Mukherjee & Hasan, 2020;& Refaat El Said, 2020). The Philippines as one of the Southeast Asian countries recorded its first COVID-19 cases on March 6, 2020, and to mitigate the spread of the COVID-19, the Philippine government suspended the classes at all levels in the National Capital Region on March 9, 2020 and later extended the suspension of classes in entire island of Luzon by declaring Enhanced Community Quarantine (ECQ) or lockdown until April 14, 2020 (Bozkurt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of digital means of teaching, in terms of collaboration between teachers and students and verifying students' knowledge, have presented promising alternatives to traditional pedagogical means [6][7][8]. However, studies in this area have been focused mainly on learning methods rather than teaching methods [9][10][11]. Meanwhile those applying the methods have not been the focus of researchers' attention; pedagogues' ability to collaborate with students and colleagues in a virtual environment, their attitude towards digital products, and evaluations of the changes to work and work conditions during the pandemic have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%